IMPLEMENTASI METODE PEMBELAJAR BERBASIS SMART GAMES DALAM MENINGKATKAN MINAT BELAJAR MAPEL PAI DI SMPIT MIFTAHUL HUDA VII - Wildan, Asep; Sheno Kusumanandi (HASBUNA : Jurnal Pendidikan Islam, 2024)
The development of science and technology which is increasingly developing is currently being used as a solution in every problem that occurs, especially in the field of education. This certainly has a positive impact on the world of education. Learning in class will not be effective if only using one method in learning but must be supported by various other learning methods so that the class atmosphere becomes more lively and does not seem monotonous. To achieve learning objectives, one of them is by choosing a strategy or learning method. Teachers innovate using various learning methods, one of which is using the smart games method. This game based method uses media in the form of quizzes and guessing games. Learning Islamic religious education is learning in one week only carried out three hours of learning. To get rid of boredom in students, teachers innovate and be creative by packaging learning with playing methods. This research is a study that aims to find out how the application of the smart game method in learning PAI at SMPIT Miftahul Huda VII. This research uses a qualitative approach and data is presented in a descriptive form. Researchers collected research data by interview, observation, and documentation techniques. Data analysis using data reduction, data presentation, and drawing conclusions. From the results of analysis of research data on Islamic religious education learning using the smart game method that: the smart game method is used as a learning evaluation, the smart game method is applied according to the material, so not all learning material only uses this method, in the application of this method is a method that is popular with students, based on the results of the research, researchers can see and conclude that learning using this method creates an active classroom atmosphere and brings pleasure and comfort to students in participating in learning activities in class.